Understanding the psychological impacts of responding to a terrorist incident - Elena A. Skryabina (Taylor & Francis Group, 2021)
Background Responding to a mass casualty event can cause significant distress, even for highly trained medical and emergency services personnel. Objective The purpose of the study was to understand more about first responders’ perspectives about their participation in major incident responses, specifically how and which individual and system factors contributed to their preparedness or may have enabled or hindered their response. The aim of the work was to improve preparedness and response for future incidents. Methods This study reports a detailed analysis of qualitative interview data from frontline staff who responded to a large mass casualty terrorist incident in the UK in 2017. Data highlighted the psychological distress caused by responding to terrorist events and thus became the focus of further, detailed analysis. Results Participants (n = 21) articulated in their own words the psychological distress experienced by many of the first responders to the event. Participants reported that they were not prepared to deal with psychological impact associated with this mass casualty terrorist incident and their role in the response, and that follow-up support was inconsistent. Multiple factors were identified as potentially increasing psychological distress. Social support provided by peers and organizational debriefs were identified as two most common support mechanisms. Organizational support was identified as inconsistent. Conclusions This research contributes to the literature the voices of first responders to UK terrorist incidents, building on existing findings while further contributing unique contextual perspectives. This research reinforces the importance of psychosocial support for those who respond to these tragic incidents, and offers a number of recommendations for organizational preparedness for future events. Abbreviations A&E: Accident and Emergency; EPRR: Emergency Preparedness, Resilience and Response; ERD: Emergency Response Department; HEPE: Health Emergency Preparedness Exercise; PHE: Public Health England; PHE REGG: Public Health England Research Ethics and Governance Group; MCI: Mass Casualty Incident; NHS: National Health Service